RNA multimerization as an organizing force for liquid-liquid phase separation - Bevilacqua, Philip C; Williams, Allison M; Chou, Hong-Li; Assmann, Sarah M (RNA (Cambridge), 2022)
RNA interactions are exceptionally strong and highly redundant. As such, nearly any two RNAs have the potential to interact with one another over relatively short stretches, especially at high RNA concentrations. This is especially true for pairs of RNAs that do not form strong self-structure. Such phenomena can drive liquid-liquid phase separation, either solely from RNA-RNA interactions in the presence of divalent or organic cations, or in concert with proteins. RNA interactions can drive multimerization of RNA strands via both base-pairing and tertiary interactions. In this article, we explore the tendency of RNA to form stable monomers, dimers, and higher order structures as a function of RNA length and sequence through a focus on the intrinsic thermodynamic, kinetic, and structural properties of RNA. The principles we discuss are independent of any specific type of biomolecular condensate, and thus widely applicable. We also speculate how external conditions experienced by living organisms can influence the formation of nonmembranous compartments, again focusing on the physical and structural properties of RNA. Plants, in particular, are subject to diverse abiotic stresses including extreme temperatures, drought, and salinity. These stresses and the cellular responses to them, including changes in the concentrations of small molecules such as polyamines, salts, and compatible solutes, have the potential to regulate condensate formation by melting or strengthening base-pairing. Reversible condensate formation, perhaps including regulation by circadian rhythms, could impact biological processes in plants, and other organisms.